PLANT GROWTH AND BIOLOGICAL PRODUCTIVITY AFTER PROCESSING WITH MICROELEMENTS - Dobrosmyslova Irina Anatolievna; Sazanova Alevtina Anatolyevna; Semenov Vladimir Grigoryevich; Tuleubayev Zhaxybay; Yesembekova Zinagul Tursynkaliyevna; Ziyaeva Gulnar (Scientific Journal of Pedagogy and Economics, 2021)
In laboratory conditions, the effect of sodium selenite and a mixture of sodium selenite and zeolite on the growth and biological productivity of peas was investigated. The soil was examined after harvesting. It was shown that the addition of both sodium selenite and the mixture of sodium selenite with zeolite to the soil with irrigation affects the development of the root system - the length of the main root in the first case increased by 16.5%, the height of the stems 30 days after planting was 29% more in comparison with the control variant, and in the second case, the length of the main root increased by 18.5%, the height of the length of the stems increased by 24% than that of the control. Processing of peas with microelements also caused a stimulation of the reproduction system: an increase in the number of inflorescences by 3 times and the number of beans in 3.4 times compared with the control. A 160-fold decrease in the selenium content and the introduction of zeolite did not cause a large difference in the obtained results (except for the number of beans - with the addition of zeolite, the number of beans increased by 8%). Biochemical indicators of pea biomass showed an increase in dry matter, in sugar content by 28.8%, but a decrease in crude protein by 17.7%, a decrease in carotene by 17.5%, nitrogen by 18% (when irrigated with sodium selenite). When treated pea with sodium selenite and zeolite, the sugar content increased by 85.5%, but it was observed a decrease in crude protein by 9.5%, in crude fat - by 16.5%, a decrease in carotene by 31.2%, a decrease in nitrogen by 9.4%. Analysis of the soil after harvesting showed in the option with the addition of sodium selenite a decrease in the amount of humus by 6.5%, mobile potassium by 18.5%, but an increase in mobile phosphorus by 6.6%, mobile calcium by 2.7%. In the option with the introduction of the mixture of sodium selenite and zeolite, no decrease in humus was observed, the content of mobile potassium decreased by 10.8%, the content of mobile phosphorus increased by 9.8%, mobile calcium by 3.5%. The acidity of the soil has not changed.